Measurement of enthalpy change of reaction and determination of equilibrium constants of glycine at different temperatures - 343062 Fong, Chin Han; Mohd Yusuf Othman, supervisor; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2007